THE MAIN DIFFERENCES BETWEEN UK AND US ENGLISH - Ubaydullayeva B.Oʼ,; Abdumoʼminova Noila, (TADQIQOTLAR, 2025)
Abstract This  article  explores  key  differences  between  British  English  and  American English based on their spelling, grammar, pronunciation , and vocabulary as well. It also  gives  some  data  about  historical  and  cultural  reasons  to  this  case  and  the development of the English language in the United States after its separation from Britain. Through detailed examples , the article regards how linguistic evolution and external  influences  contributed  this  distinct.  Understanding  these  differences  is essential for effective inernational communication and language learning.